O requebrado que virou moda: tendências, identidade para o mercado e Carmem Miranda (ModaPalavra e-periódico, 2012)
In Modernity fashion system behaves like a social engine driven by the pursuit of innovation, shown by appearance and linked to desire, pleasure, power relations and social tensions. Therefore, this study intends to analyze the construction of a Brazilian fashion identity towards the international market, focused on differentiation and innovation through the character of Carmen Miranda and her “baiana”. It defines the concept of trends and targeting behaviors. It approaches the formation of a Brazilian identity focused on the market and Carmen Miranda as a symbol of this trend. It debates the appropriation of Carmen Miranda’s image by fashion system at a recent period (2009-2011), when her image becomes an icon of a fashion trend and symbolizes an identity for the market, confirmed by Prada’s spring/summer 2011 Collection. The research was carried out from broadcasted images of Carmen Miranda and records of its appropriation in fashion, literature, print and digital media, and virtual collections.
Keywords: Carmen Miranda; Fashion Trend; Identity